On The Novel Action of Melanolysis by a Leaf Extract of Aloe vera and Its Active Ingredient Aloin, Potent Skin Depigmenting Agents - Ali, Sharique A.; Galgut, Jyoti M.; Choudhary, Ram K. (Planta Medica, 2012)
The present study was carried out to investigate the effects of an Aloe vera leaf extract, along with its standard active ingredient aloin, on the isolated tail melanophores of Bufo melanostictus tadpoles, which are a type of disguised smooth muscle cells offering excellent in vitro opportunities for studying the effects of pharmacological and pharmaceutical agents. It was found that the leaf extract of A. vera and its active ingredient aloin induced powerful, dose-dependent, physiologically significant melanin aggregating effects in the isolated tail melanophores of B. melanostictus similar to those of adrenaline per se. These preliminary findings clearly demonstrate that the extract of A. vera and its active ingredient aloin cause melanin aggregation leading to skin lightening via alpha adrenergic receptor stimulation. The present study opens new vistas for the use of A. vera regarding its clinical application as a new nontoxic melanolytic agent for the treatment of hyperpigmentation.
Keywords: Aloe vera L.; Liliaceae; aloin; adrenoceptors; depigmenting compound; skin lightening